PERANCANGAN SISTEM PENGAIRAN OTOMATIS PADA MEDIA TANAMAN BUAH DALAM POT (TABULAMPOT) BERBASIS INTERNET OF THINGS - Effendy Candra Sasmoro; Devi Yunita (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The use of technology in agriculture is expected to increase the yield of fruit farming, especially the cultivation of fruit plants in pots. This situation is supported by Green Tabulampot Nanda which has various kinds and types of fruit plants in pots such as avocado, guava, mango, orange, longan which is used in containers in the form of pots, panter bags and tabulampot using planting media in the form of soil, husks, and manure or compost that easily absorbs water so tabulampot requires regular watering. By utilizing the Wemos D1 WiFi ESP8622 microcontroller hardware which is used as an internet connection between the Wemos D1 WiFi ESP8622 to a web server via the internet network and the Soil Moisture Sensor is an indicator used as a soil moisture detector which is accessed by the microcontroller to be stored in the database so that it is expected to be able to makes it easier for tabulampot owners to monitor and irrigate tabulampot automatically based on soil moisture value settings and scheduled time settings so that tabulampot can be fulfilled so that plants are healthy, able to flower and bear fruit as desired.